Brain Structural Signature of RFC1‐Related Disorder. Issue 11 (9th July 2021) - Matos, Paula Camila A.A.P.; Rezende, Thiago J.R.; Schmitt, Gabriel S.; Bonadia, Luciana Cardoso; Reis, Fabiano; Martinez, Alberto R.M.; de Lima, Fabrício D.; Bueno, Manoella Guerra de Albuquerque; Tomaselli, Pedro José; Cendes, Fernando; Pedroso, José Luiz; Barsottini, Orlando G.P.; et al.
Abstract: Background: The cerebellar ataxia, neuropathy, and vestibular areflexia syndrome was initially described in the early 1990s as a late‐onset slowly progressive condition. Its underlying genetic cause was recently mapped to the RFC1 gene, and additional reports have expanded on the phenotypic manifestations related to RFC1, although little is known about the pattern and extent of structural brain abnormalities in this condition. Objective: The aim is to characterize the structural signature of brain damage in RFC1 ‐related disorder, correlating the findings with clinical symptoms and normal brain RFC1 expression. Methods: We recruited 22 individuals with molecular confirmation of RFC1 expansions and submitted them to high‐resolution 3T magnetic resonance imaging scans. We performed multimodal analyses to assess separately cerebral and cerebellar abnormalities within gray and white matter (WM). The results were compared with a group of 22 age‐ and sex‐matched controls. Results: The mean age and disease duration of patients were 62.8 and 10.9 years, respectively. Ataxia, sensory neuronopathy, and vestibular areflexia were the most frequent manifestations, but parkinsonism and pyramidal signs were also noticed. We found that RFC1 ‐related disorder is characterized by widespread and relatively symmetric cerebellar and basal ganglia atrophy. There is brainstem volumetric reduction along all its segments. Cerebral WM is also involved—mostly the corpus callosum and deep tracts, but cerebral cortical damage is rather restricted. Conclusion: This study adds new relevant insights into the pathophysiological mechanisms of RFC1 ‐related disorder. It should no longer be considered a purely cerebellar and sensory pathway disorder. Basal ganglia and deep cerebral WM are additional targets of damage. © 2021 International Parkinson and Movement Disorder Society